Functional-semantic peculiarities of translating cybersecurity terminology - Yuldoshev Ulugbek Ravshanbekovich (Universal Teaching and Learning Journal, 2025)
Purpose: This study aims to analyze the challenges and strategies involved in translating English cybersecurity terminology into Uzbek, with particular attention to preserving the functional and semantic features of the source terms. Research methodology: The research applies a descriptive-analytical approach by examining existing terminological units in English and their Uzbek equivalents. Comparative linguistic analysis and semantic mapping are used to identify patterns of borrowing, adaptation, and equivalence in translation. Results: The findings indicate that most Uzbek cybersecurity terminology originates from English, often entering through direct borrowing or partial adaptation. While many terms maintain functional accuracy, semantic distortions occur when literal translation is applied without contextual consideration. The research also highlights that some terminological units enrich the Uzbek lexicon, while others pose challenges in achieving precise equivalents due to cultural and linguistic differences. Conclusions: Translating cybersecurity terms requires strategies that balance linguistic accuracy with functional clarity. The study concludes that a hybrid approach—combining direct borrowing with contextual adaptation—is the most effective way to maintain the semantic integrity of specialized terms. Limitations: The study is limited to selected cybersecurity terms and does not encompass all branches of information technology. Broader corpus-based research may be needed to generalize the findings. Contribution: This research contributes to translation studies and applied linguistics by providing insights into the mechanisms of term transfer between English and Uzbek, offering practical recommendations for translators, linguists, and ICT professionals.